Pengaruh Pendidikan Kesehatan terhadap Peningkatan Konsumsi Makanan Bergizi pada Anak Remaja di SMP Santo Ignasius Johor Medan - Marida Marbun; Asriwati Asriwati; Nuraini Nuraini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Nutrition is a contribution to a person's health and development. Good nutrition can build a strong immune system, prevent disease, and improve health. The purpose of the study was to determine the effect of health education on increasing the consumption of nutritious food. This type of research is research quasi-experimental using the pretest-posttest design method, namely by providing a pretest (initial observation) before the intervention is carried out, after the intervention is given, then a posttest (final observation) is carried out. Health education in the form of balanced nutrition animation videos, balanced nutrition PPTs and food models. The statistical test used was Paired test T-Test. The results of the analysis of the pair t-test pre-test and post- test knowledge obtained a p value = 0.000, so it can be concluded that there is an effect of health education on increasing knowledge of nutritious food consumption. The results of the analysis of the pair t-test pre-test and post- test attitude obtained a p value = 0.000, which means is an effect of health education on increasing attitudes of nutritious food consumption. The results of the analysis of the pair t-test pre-test and post- test Action obtained a p value = 0.159, which means so it can be concluded that there is no effect of health education on increasing actions to consume nutritious food. This study is that there is an influence of health education on increasing knowledge and attitudes towards consuming nutritious food at SMP Santo Ignasius Johor. Video media can be recommended as an effective communication media because it can contain a lot of information about educational materials